Model Keperawatan Keluarga Peka Budaya Sunda dalam Meningkatkan Pengetahuan Keluarga dan Menurunkan Kadar Gula Darah pada Diabetisi Lansia - Siti Badriah (Jurnal Keperawatan Silampari, 2021)
This study aims to determine the Sundanese culture-sensitive family nursing model's effectiveness in increasing family knowledge and reducing blood sugar levels in older people with diabetes. The research design used in this study was a quasi-experimental pre and post-test. The results showed an increase in the mean family knowledge and blood sugar levels of older people with diabetes in the intervention group was higher than the control group with a p-value of 0.000. In conclusion, the Sundanese culture-sensitive family nursing model can increase family knowledge in caring for older people with diabetes and impact controlling blood sugar levels after the model intervention. Keywords: Sundanese Culture, Older People with Diabetes, Blood Sugar, Knowledge